2020
DOI: 10.1186/s12920-020-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, genomics and networking analyses of a high-altitude native American Ecuadorian patient with congenital insensitivity to pain with anhidrosis: a case report

Abstract: Background: Congenital insensitivity to pain with anhidrosis (CIPA) is an extremely rare autosomal recessive disorder characterized by insensitivity to pain, inability to sweat and intellectual disability. CIPA is caused by mutations in the neurotrophic tyrosine kinase receptor type 1 gene (NTRK1) that encodes the high-affinity receptor of nerve growth factor (NGF). Case presentation: Here, we present clinical and molecular findings in a 9-year-old girl with CIPA. The highaltitude indigenous Ecuadorian patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…was inherited from his father, and the missense variant, c.2020G>T (p.Asp674Tyr), classified as likely pathogenic by ACMG classification, was inherited from his mother. c.2020G>T (p.Asp674Tyr) has also been reported previously (López‐Cortés et al., 2020). In patient 3, compound heterozygous variants c.2303C>T (p.Pro768Leu) and c.574‐156_850+1113del (exons 5‐7 del) were identified.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…was inherited from his father, and the missense variant, c.2020G>T (p.Asp674Tyr), classified as likely pathogenic by ACMG classification, was inherited from his mother. c.2020G>T (p.Asp674Tyr) has also been reported previously (López‐Cortés et al., 2020). In patient 3, compound heterozygous variants c.2303C>T (p.Pro768Leu) and c.574‐156_850+1113del (exons 5‐7 del) were identified.…”
Section: Resultssupporting
confidence: 82%
“…The frequency of this variant is extremely low in the gnomAD v2.1.1 dataset (total allele frequency: 0.0000041, PM2). It has been observed as a compound heterozygote with other variants, suggesting the attenuated nature of this variant (López‐Cortés et al., 2020; Miranda, Di Virgilio, et al., 2002; Miura et al., 2000). The alternative variant situated in the tyrosine kinase domain, c.2303C>T (p.Pro768Leu), was documented to exhibit milder symptoms with retained cognitive function and pain sensation (Jung et al., 2013; Ohto et al., 2004; Tanaka et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An early disease onset in 5q SMA types I and 0 illustrates the imperative need for implementing the aforementioned up-to-date strategies that might include newborn or even prenatal SMA genetic screening. Quantitative real time PCR (qPCR) seems to be an effective method for genetically testing newborns [ 7 , 145 , 146 ]. At present, nine countries have implemented SMA newborn screening (NBS) programs, Taiwan and the US being the leading nations with 90% and 70% of newborns screened for SMA, respectively [ 4 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…At the same time, insensitivity to pain and thermal sensations could lead to multiple fractures, burns and sometimes self-mutilation of fingers, tongue, and lips. Autonomic dysfunction leads to manifestations like anhidrosis and fever ( 4 , 5 ). In recent years, with the accumulation of clinical experience and the development of genome sequencing technology, it has been found that the recessive mutation of NTRK1 may lead to CIPA.…”
Section: Discussionmentioning
confidence: 99%